THE ROLE OF ISLAMIC ECONOMICS IN ECONOMIC CRISES - Amro Halfaoui; Sabbar Dahham Sabbar; Siradjuddin Siradjuddin (International Conference on Social and Islamic Studies, 2021)
This research is a step on the way to the solutions that were presented From the general economic perception in Islam, which  Explains the role of adherence to the controls of the Islamic economy in limiting global financial crises and its ability to achieving economic and financial stability.